Maps for Jackie - Labbe, Jason (BlazeVOX Books, 2020)
"Poetry's natural habitat is one of detail, radiant or tarnished, an intimate geography that draws us close to where presence is an act of perception: world into word. In Maps for Jackie, Jason Labbe navigates a terrain of singular encounters and incidents, tactile, luminous and animated by the sensuous abrasions and comforts of the heartmind as they touch down on his, and our, present: white leaf is like a moth / wing I'd fix to her shoulder.--Ann Lauterbach"--The back cover
Keywords: 21st century; American poetry; dept.eng; faculty_collection